Meta-analysis of the prognostic role of perioperative platelet count in posthepatectomy liver failure and mortality - Mehrabi, Arianeb; Golriz, Mohammad; Khajeh, Elias; Ghamarnejad, Omid; Probst, Pascal; Fonouni, Hamidreza; Mohammadi, Sara; Weiss, Karl Heinz; Büchler, Markus W. (The British journal of surgery, 2018)
BACKGROUND: Emerging evidence suggests that the perioperative platelet count (PLT) can predict posthepatectomy liver failure (PHLF). In this systematic review and meta-analysis, the impact of perioperative PLT on PHLF and mortality was evaluated. - METHODS: MEDLINE and Web of Science databases were searched systematically for relevant literature up to January 2018. All studies comparing PHLF or mortality in patients with a low versus high perioperative PLT were included. Study quality was assessed using methodological index for non-randomized studies (MINORS) criteria. Meta-analyses were performed using Mantel-Haenszel tests with a random-effects model, and presented as odds ratios (ORs) with 95 per cent confidence intervals. - RESULTS: Thirteen studies containing 5260 patients were included in the meta-analysis. Two different cut-off values for PLT were used: 150 and 100/nl. Patients with a perioperative PLT below 150/nl had higher PHLF (4 studies, 817 patients; OR 4·79, 95 per cent c.i. 2·89 to 7·94) and mortality (4 studies, 3307 patients; OR 3·78, 1·48 to 9·62) rates than patients with a perioperative PLT of 150/nl or more. Similarly, patients with a PLT below 100/nl had a significantly higher risk of PHLF (4 studies, 949 patients; OR 4·65, 2·60 to 8·31) and higher mortality rates (7 studies, 3487 patients; OR 6·35, 2·99 to 13·47) than patients with a PLT of 100/nl or greater. - CONCLUSION: A low perioperative PLT correlates with higher PHLF and mortality rates after hepatectomy.
Gesehen am 25.03.2020